Public sector reform in South Africa 1994-2021 - Cameron, Robert (Professor of Public Administration) (Emerald Publishing Limited, 2022)
Public Sector Reform in South Africa 1994-2021 is an examination of specific public sector reforms in three core Public Administration areas in the democratic South Africa: political-administrative relationships, the delegation of authority to senior managers and performance management. Comprehensively spanning a critical period from 1994 to the current day, this collection constitutes the first systematic study of public sector reform in the gamut of the democratic era in the country. The author traces developments of policy following a rapid political shift, shedding light on previously unexplored evolving structures and systems. The Public Policy and Governance series brings together the best in international research on policy and governance issues. Books within the series are authored and edited by experts in the field and present new and insightful research on a range of policy and governance issues across the globe.
Keywords: Public administration -- South Africa.; Decentralization in government -- South Africa.; Delegation of authority.; Political Science -- Public Affairs & Administration.; Public administration.; elektronické knihy; electronic books